Collected Works - Marx, Karl; Engels, Frederick (Moscow Progress publishers, 1975)
Library has Vol.1-14, 16-17
Contents
v.1: Marx : 1835-1843
v.2: Engels: 1838-1842
v.3: Marx and Engels: 1843-44
v.4: Marx and Engels:1944-45
v.5: Marx and Engels: 1845-47
Keywords: Marx,Karl--Collected works; Engles,Frederick--Collected works